Effects of Primary Healthcare Quality and Effectiveness on Hospitalization Indicators in Brazil - Bruna Leão Freitas; Maria Luisa de Oliveira Collino Antiga; Flavia Mori Sarti (Journal of Market Access & Health Policy, 2025)
Advances in primary healthcare coverage for the improvement in health outcomes at the population level comprise a major goal of public policies of health, particularly considering increases in hospitalization costs linked to chronic diseases in recent decades. Previous evidence shows the positive effects of access to primary healthcare on hospitalization indicators in high-income countries; however, there is a lack of literature on the subject in Latin American countries. Thus, the present study proposes a quantitative investigation on connections between primary healthcare quality and effectiveness in relation to hospitalization indicators, in addition to the identification of its effects on inequalities in hospitalizations in Brazil. The study was based on an empirical analysis of data from five cross-sectional surveys representative at the population level conducted by the Brazilian Institute for Geography and Statistics (IBGE) in 1998, 2003, 2008, 2013, and 2019. Information on the demographic, socioeconomic, and health characteristics of individuals compatible across surveys were included in the analyses, in addition to data on household and survey characteristics. The statistical analyses were based on the estimation of logistic regression models for the exploration of effects of primary healthcare quality and effectiveness on hospitalizations, inpatient days, and perception of quality of hospital care. Furthermore, the estimation of concentration indexes and their disaggregation allowed to verify trends and determinants of inequalities in hospitalization indicators in Brazil throughout the period. The results indicate that primary healthcare effectiveness is associated with the lower occurrence and frequency of hospitalizations, and a lower length of stay in hospitals. Primary healthcare quality was associated with the perception of higher quality of hospital care. Trends in hospitalization indicators showed reduction in inequalities towards low-income individuals from 1998 to 2013, and primary healthcare quality presented minor influence on inequalities in hospitalizations, inpatient days, and perception of quality of hospital care.